Women and Men Differ in Relative Strengths in Wisdom Profiles: A Study of 659 Adults Across the Lifespan - Treichler, Emily B. H.; Palmer, Barton W.; Wu, Tsung-Chin; Thomas, Michael L.; Tu, Xin M.; Daly, Rebecca; Lee, Ellen E.; Jeste, Dilip V. (Frontiers in Psychology, 2022)
Wisdom is a multi-component trait that is important for mental health and well-being. In this study, we sought to understand gender differences in relative strengths in wisdom. 659 individuals aged 27-103 years completed surveys including the 3-Dimensional Wisdom Scale (3D-WS) and the San Diego Wisdom Scale (SD-WISE). Analyses assessed gender differences in wisdom and gender’s moderating effect on the relationship between wisdom and associated constructs including depression, loneliness, well-being, optimism, and resilience. Women scored higher on average on the 3D-WS but not on the SD-WISE. Women scored higher on compassion-related domains and on SD-WISE Self-Reflection. Men scored higher on cognitive-related domains and on SD-WISE Emotion Regulation. There was no impact of gender on the relationships between wisdom and associated constructs. Women and men have different relative strengths in wisdom, likely driven by sociocultural and biological factors. Tailoring wisdom interventions to individuals based on their profiles is an important next step.